Belowground biodiversity in a Mediterranean landscape: relationships between saprophagous macroarthropod communities and vegetation structure (Biodiversity and …, 1999)
Millipedes and woodlice were sampled at 27 sites in a mosaic landscape in order to establish the extent to which the macroarthropod community changed with dierent plant for- mations. Multivariate analyses conducted on abundance data for ten species revealed four main types of macroarthropod communities. This classi®cation was highly correlated with vegetation structure and particularly the degree of openness of the sites. Communities dominated by Om- matoiulus rutilans (Julidae) occurred in open grassland; those dominated by Glomeris marginata (Glomeridae) plus Porcellio gallicus (Porcellionidae) were found at the least open sites, with a high oak cover; communities with a high proportion of the endemic glomerid Glomeris annulata oc- curred in semi-open sites with a substantial cover of shrubs. Species diversity was signi®cantly higher at the semi-open sites, this being interpreted as an edge eect. Population density and biomass were lower at wooded sites. In the context of a regional trend towards woodland ex- pansion, the results are discussed from the viewpoint of conserving the pool of millipede and woodlouse species and of maintaining the abundance of saprophagous macroarthropods in the region's ecosystems.